Improvement in Brazilian barley breeding: Changes in developmental phases and ecophysiological traits - Rodrigues, Osmar; Minella, Euclydes; Costenaro, Edson Roberto; Scariotto, Silvia; Marchese, José Abramo (Frontiers in Plant Science, 2022)
Despite recognizing the importance of genetic improvement in the production of barley grains, little information is available on the contribution of phenological development to the genetic improvement of Brazilian barley. Field experiments were carried out between 2011 to 2013, in the absence of biotic and abiotic stresses and with preventive lodging control. Five two-rowed spring barley cultivars, released between 1968 and 2008, were evaluated. Although there was no significant association in the cycle length (Emergence - Anthesis) of the cultivars with the year of release, the genetic improvement increased the proportion of the Doble ridge - Maximum number of spikelet primordia/Maximum number of spikelet primordia - anthesis period to the total time to anthesis. The period between DR-MNP was increased in modern cultivars, to the detriment of the Doble ridge - Maximum number of spikelet primordia period. However, the duration of the period between emergences to the double ridge (vegetative phase) was not altered in the analyzed period. Barley breeding in Brazil did not change the total number of leaves on the main stem but caused an increase in the number of leaves earlier in the development, favoring the high level of tillering. The leaf architecture of modern barley was altered towards a more vertical inclination (erectophilic canopy), allowing the penetration of photosynthetically active radiation into the crop canopy.